2020
DOI: 10.1017/jfm.2020.482
|View full text |Cite
|
Sign up to set email alerts
|

Correlations for inclined prolates based on highly resolved simulations

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 46 publications
(120 reference statements)
8
17
0
Order By: Relevance
“…Overall, the flow past the cylinder looks massively separated in between the free streamlines f s − and f s + , the position of the 'eye' governing the flow structure in the intermediate region. A similar open separation configuration was recently observed over inclined prolate spheroids in the range 5 ≤ Re ≤ 100 in [34].…”
Section: A Flow Structuresupporting
confidence: 82%
“…Overall, the flow past the cylinder looks massively separated in between the free streamlines f s − and f s + , the position of the 'eye' governing the flow structure in the intermediate region. A similar open separation configuration was recently observed over inclined prolate spheroids in the range 5 ≤ Re ≤ 100 in [34].…”
Section: A Flow Structuresupporting
confidence: 82%
“…Overall, the flow past the cylinder looks massively separated in between the free streamlines f s − and f s + , the position of the 'eye' governing the flow structure in the intermediate region. A similar open separation configuration was recently observed over inclined prolate spheroids in the range 5 ≤ Re ≤ 100 in [33]. We now make use of the numerical results to build approximate force and torque laws valid for |θ| 30 • and Re 10 in the stationary non-axisymmetric flow regime.…”
Section: A Flow Structuresupporting
confidence: 59%
“…During the last decade, a number of notable works to provide correlations to calculate drag and lift are reported for finite Reynolds numbers [24,25,26,27,28,29]. Majority of those are obtained through data fitting and satisfy the theoretical formulation at the limiting cases.…”
Section: Introductionmentioning
confidence: 99%
“…Forces on the spherical particle in the vicinity of a rough wall for liner shear flow have been estimated by Lee and Balachandar [8]. Frohlich et al [28] have also performed a number of simulations using the Cartesian cut cell method for an ellipsoid in an unbounded uniform flow. They have reported that beyond certain aspect ratio (> 3), the flow is not influenced much with the aspect ratio.…”
Section: Introductionmentioning
confidence: 99%